2017
DOI: 10.1002/app.45936
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of mechanical strength associated with interfacial tension between barium titanate and acrylonitrile–butadiene rubber with different acrylonitrile contents by surface modification

Abstract: Acrylonitrile–butadiene rubber (NBR) with different acrylonitrile (ACN) contents was filled with barium titanate (BT) to prepare the polymer dielectrics. The neat NBR, NBR/untreated BT, and NBR/bis‐(γ‐triethoxysilylpropyl)‐tetrasulfide (silane coupling agent KH845‐4) modified BT (MBT) composites were prepared. At low ACN content (ACN content 20 wt %), the tensile strength of the NBR/MBT composites increased by 173.6% from 2.69 to 7.36 MPa compared to the neat NBR. The pleasing results were not found in those c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Although the effect of different acrylonitrile contents and silane coupling modified BT on NBR filled BT has been described by Zhu et al, 11 the BT loading was not reported. While Amin et al 22 have presented the electrical properties of NBR/BT composites, many related details including cure characteristics, mechanical, dynamic mechanical, thermal and morphological properties have not been investigated.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although the effect of different acrylonitrile contents and silane coupling modified BT on NBR filled BT has been described by Zhu et al, 11 the BT loading was not reported. While Amin et al 22 have presented the electrical properties of NBR/BT composites, many related details including cure characteristics, mechanical, dynamic mechanical, thermal and morphological properties have not been investigated.…”
Section: Introductionmentioning
confidence: 92%
“…10 Nevertheless, the lack of interactions between a polymer matrix and an inorganic filler causes agglomeration of the filler, resulting in poor mechanical properties of the final composite. 11 The ways to increase interactions between fillers with a polymer include modifying either the filler surfaces or the available polar groups of the polymers. 12 Thus, some studies have investigated modifying the BT [13][14][15][16][17] and the application of coupling agents 10,[18][19][20] to improve the compatibility of BT with a polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[102] Like TPU, the endogenous heat of NBR generated during actuation is too large to shorten the its service life. [103] The main chains of silicone rubber are composed of silicon and oxygen atoms alternately. [104] Ordinary silicone rubber is mainly consisted of siloxane segments containing methyl and a small amount of vinyl.…”
Section: Thermoset Elastomersmentioning
confidence: 99%
“…[76] It is reported that commercialized coupling agents are effective in surface modification of BaTiO3 filled in elastomers, because coupling agents not only reduce the surface energy of particles, but also introduce functional groups to the surface of BaTiO3 particles, shown in Figure 9. [103,120] ( Figure 9) Figure 9 Reaction mechanism model among BaTiO3 (BT), silane coupling agent KH845-4 and molecular chain [103] As shown in Figure 10, such functional groups can participate into the vulcanization process to form extra crosslinks with polymer matrix, which improves the mechanical properties of composites. [120] ( Figure 10) with NDZ109 treated BaTiO3; (D) EPDM with KH570 treated BaTiO3; [120]…”
Section: Modification Of Batio3 Particles By Surfactantmentioning
confidence: 99%